Desenvolvimento de um dilatômetro interferométrico e determinação dos parâmetros termo-ópticos de sistemas vítreos em função da temperatura - Barboza, Marcio José (2006)
In this work we developed an interferometric dilatometer to determine the linear thermal expansion coefficient (α) as a function of temperature. This technique is based on the interference phenomenon of the electromagnetic radiation in parallel surfaces, whose pattern of fringe is altered by the thickness variation of the sample with the heating. The interferometric dilatometer presents the great advantage of being a quantitative technique, not being necessary any previous calibration. The characterization of the system was carried out using the samples: polymethylmethacrylate (PMMA), aluminum and stainless steel, whose results as a function of temperature are in excellent agreement with the data of the literature, showing that our assembly presents precision in the order of 5x10-7K-1. The behavior of the linear thermal expansion coefficient as a function of temperature was studied for the calcium aluminosilicate (CAS), low silica calcium aluminosilicate doped with Nd2O3 (LSCAS), tellurite and "oda-lime" glasses. Associating these values with the results obtained by the multiple beans interferometric technique, were determined the temperature coefficient of the optical path length (dS/dT), the thermal coefficient of the optical path length (dn/dT) and the thermal coefficient of the electronic polarizability (φ).The termo-optical parameters for the glass CAS shows a significant reduction compared with the obtained for LSCAS. This can be attributed to the reduction of the non-bridging oxygen with the increasing of the SiO2 concentration. Although the glass telureto has presented the largest value of the coefficient of linear thermal expansion, the dS/dT value is smaller than that obtained for LSCAS and CAS. This result is consequence of the negative value of dn/dT presented by this glass, what was attributed to the competition between the effect of the thermal expansion and the temperature coefficient of the electronic polarizability.